Efeitos centrais da cumarina (1,2-Benzopirona) : estudo comportamental e neuroquímico em córtex pré-frontal e hipocampo de camundongos - Lucetti, Elaine Cristina Pereira (2010)
Coumarin (1,2-benzopyrone) is an aromatic compound found in many plant species. This study proposed to evaluate the coumarin actions in behavioral models of anxiety, depression and sedation activity, such as the open field, rota rod, elevated plus maze (EPM), hole board and tail suspension, still looking to clarify mechanisms by which this compound acts, through amino acids determination studies in mice prefrontal cortex and hippocampus by HPLC (High Performance Liquid Chomatography). The coumarin (CUM) was administered acutely in all tests, at doses of 5, 20 or 40 mg/kg, by intraperitoneal route. The results show that CUM, in all used doses, decreased the locomotor activity, the number of rearing and grooming in open field test, suggesting a possible sedative action. In the rota rod the coumarin did not alter the motor coordination or caused muscular deficit in animals. This suggests that the depressant effect of coumarin should not be exercised by peripheral neuromuscular blockade, but possibly the effects must involve neurons that control the central depressive activity. In the EPM and hole board test, coumarin proved its anxiogenic effect, as it reduced all examined parameters in the EPM, as NEOA, PEOA, TPOA and PTOA, as well as the number of head dips in the hole board. This opposite effect to diazepam was not reversed by flumazenil (benzodiazepine antagonist). This suggests that coumarin does not act in a similar manner to benzodiazepines. Still aiming to clarify the changes in animals locomotor activity, it was administered levodope + carbidope (L-DOPA), which led to a small increase in the locomotor activity, compared to CUM group. When associated to haloperidol (HALO) - dopaminergic antagonist, L-DOPA had its effects reversed. HALO + CUM caused greater interference in locomotion, as a synergic effect. The coumarin did not show antidepressant effect in the tail suspension test, because it increased the immobility time of animals. Imipramine (antidepressant) decreased this parameter. In the determination of amino acids neurotransmitters it was observed an increase in the GABA levels in the prefrontal cortex, similar to diazepam, which may partly explain the decrease in locomotor activity. The levels of glutamate, glycine and taurine also increased in the group treated with coumarin 20 mg/kg. In the hippocampus, significant changes occurred in levels of glutamate, which were reduced. It follows, therefore, that the CUM has sedative, anxiogenic and depressant activities. These actions can be linked to an increase or decrease of excitatory and inhibitory amino acids levels and dopaminergic involvement. The anxiogenic effect of coumarin seems to involve the dopamine participation on striatum. Increased levels of taurine leads to a balance in the glutamate levels, which may explain the anxiogenic effect and possible neuroprotective of coumarin. The coumarin demonstrate sedative and anxiogenic action in CNS probably caused by dopaminergic antagonism modulated by gabaergic system, mainly glutamatergic in the prefrontal cortex.